1986
DOI: 10.3109/00498258609043512
|View full text |Cite
|
Sign up to set email alerts
|

The microbial metabolism of condensed (+)-catechins by rat-caecal microflora

Abstract: The metabolism of 2,3-trans-3,4-trans-3,5,7,3',4'-pentahydroxy-4-(2,4,6-trihydrox yphenyl)-flavan and 2,3-trans-3,4-trans-3,5,7,3',4',-pentahydroxy-4-(2,3-trans-3,5,7,3 ', 4'-pentahydroxyflavanyl-[8])-flavan in vitro by rat-caecal microflora was investigated. Metabolites were extracted and enriched by column chromatography and preparative h.p.l.c., while structural determination was carried out using comparative g.l.c.-mass spectrometry and p.m.r. spectrometry. The metabolites identified were derivatives of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
5
32
3
Order By: Relevance
“…3). The possible depolymerization of dimeric structures into monomeric units, firstly proposed by Groenewoud et al, 64 has been recently confirmed to occur but to a lesser extent, 54,61 representing less than 10% in the case of procyanidin B2. 61 Other microbial metabolites arising exclusively from the catabolism of dimeric procyanidins have recently been identified, such as 5-(2 0 ,4 0 -dihydroxyphenyl)-2-ene-valeric acid, as well as other compounds which have been tentatively identified as derivatives from the A-ring of the upper unit, including the interflavanic bond.…”
Section: Iii2 Metabolites Arising From the Catabolism Of Dimeric Promentioning
confidence: 82%
“…3). The possible depolymerization of dimeric structures into monomeric units, firstly proposed by Groenewoud et al, 64 has been recently confirmed to occur but to a lesser extent, 54,61 representing less than 10% in the case of procyanidin B2. 61 Other microbial metabolites arising exclusively from the catabolism of dimeric procyanidins have recently been identified, such as 5-(2 0 ,4 0 -dihydroxyphenyl)-2-ene-valeric acid, as well as other compounds which have been tentatively identified as derivatives from the A-ring of the upper unit, including the interflavanic bond.…”
Section: Iii2 Metabolites Arising From the Catabolism Of Dimeric Promentioning
confidence: 82%
“…These compounds are then available for absorption by the colon [67,69]. The importance of this microbial degradation pathway needs to be studied further.…”
Section: Biotransformation and Pharmacokinetics Of Pcsmentioning
confidence: 99%
“…The degree of polymerization of proanthocyanidins has also been reported to decrease in the rat small intestine (Abia & Fry, 2001). Other authors also suggested that procyanidin dimers might be degraded into catechin monomers by microflora in the colon although they did not report the presence of catechin as an intermediate breakdown product in their in vitro experiments (Groenewoud & Hundt, 1986;Déprez et al 2000). In the present study, no catechin was detected in the plasma or urine of the rats fed the meal containing 20 mg purified procyanidin dimer B 3 indicating that this procyanidin was not cleaved into a bioavailable source of catechin in the stomach or large intestine.…”
Section: Discussionmentioning
confidence: 46%
“…Furthermore, more biological effects of procyanidins in inner tissues could be mediated by some metabolites formed in the colon and then absorbed through the colon barrier. Procyanidin B 3 dimer and procyanidin polymers can be degraded by microflora in the large intestine into bioavailable phenolic acids similar to those formed from catechin itself (Scheline, 1970;Groenewoud & Hundt, 1986;Déprez et al 2000). Studies have identified mono-and dihydroxylated phenylpropionic, phenylacetic and hippuric acid as well as various phenylvalerolactones as flavanol metabolites in plasma (Das, 1971;Hackett et al 1983;Pietta et al 1998;Li et al 2000).…”
Section: Discussionmentioning
confidence: 99%